Bacteriological and Mycological Profile of Urinary Tract Infections among Diabetic Patients at a Tertiary Care Centre - S. Patil, Dr. Bhagyashree; Gopi, Dr. Anjana; Jain, Dr. Swati; Samreen, Dr. Faiza; C. K., Dr. Madhulatha (International Journal of Innovative Research in Medical Science, 2018)
Introduction - Urinary tract infections (UTIs) are among the most common bacterial infections. Patients with diabetes often have increased antimicrobial resistance and complications. The incidence of Methicillin resistance Staphylococcus aureus (MRSA), extended spectrum beta lactamases (ESBL) and Metallo-beta lactamases (MBL) producing organisms have been steadily increasing over the past few years resulting in limited therapeutic options. Material and Methods - It is a prospective study conducted at a tertiary care centre for a period of 18 months from December 2014- June 2016. A total of 200 urine samples of clinically suspected UTI among diabetic patients were collected aseptically. The isolates were identified by conventional methods along with HiCrome UTI agar and Antibiotic susceptibility testing (AST) was performed using Kirby Bauer disc diffusion method according to CLSI guidelines. Staphylococcus aureus (S. aureus) isolated was further studied for MRSA using Cefoxitin disc diffusion test. ESBL and MBL producers among gram negative isolates were detected by combined disc diffusion test as per CLSI guidelines. The Candida isolates were speciated by the germ tube test and chromogenic media. Antifungal susceptibility testing by Kirby Bauer disc diffusion method to fluconazole, voriconazole and amphotericin B was performed. Results - Of 200 samples, 100 (50%) yielded growth. Escherichia coli (E.coli) (32.43%) being the most common isolate followed by Klebsiella pneumoniae (K.pneumoniae) (18.91%). MRSA was observed in 50% (three out of six) S. aureus isolates. ESBL production was observed in 47.36% of all gram negative isolates and MBL production was observed in 50% of all nil-fermenting gram negative isolates. Out of 22 Candida isolates, 20 (90.9 %) were susceptible to amphotericin-B followed by voriconazole 19 (86.3%). Conclusion - Most of the isolates were multidrug resistant making available therapeutic choices limited.So antibiotic surveillance, infection control practices and an effective antibiotic policy are required to address this problem of increasing resistance.